Effort to Improve Public Education Performance to Reduce Traffic Violation at Pekalongan City Police Office Juridiction - M. Dito Anugerah (Advances in Police Science Research Journal, 2022)
Traffic offences are traffic issues of specific concern to the Police Traffic Unit. This study describes traffic offences in the Pekalongan City Police Department. The purpose of this study is to describe the implementation of the Traffic Public Education and Community Service and the improvement of Traffic Public Education performance by the Pekalongan City Police Security and Safety Unit in traffic violations in the jurisdiction of the Pekalongan City Police. To improve and implement Public Traffic Education which is a preventive effort to tackle the problem of traffic violations in Pekalongan City, the Pekalongan City Police Security and Safety Unit is guided by the Implementation Instruction of the National Police Chief No. Pol: Juklak /05/V/2003 regarding the Implementation of Traffic Public Education. The analytical knife to describe the purpose of this research uses the skills theory of Hutapea and Taha. And the theory of management principles and aspects of management by George R. The approach used in this study is a qualitative approach and the collection of data using interview, observational and document-based techniques. Based on the discussion of the results of the key research, there are still many traffic violations, especially violations of traffic signs with the type of four-wheeled vehicle and in the adult age group, it is necessary to improve the planning, organization, implementation, and supervision of the human element, methods, materials and machines in the implementation of the social education program. And there have also been efforts to improve performance in reducing traffic violations committed by the Pekalongan City Police Security and Safety Unit, but there are still some weaknesses and obstacles based on the knowledge, abilities, and attitudes of members in the Pekalongan City Police Security and Safety Unit.